A non-standard approach to a market with boundedly rational consumers and strategic firms. Part I: A microfoundation for the evolution of sales - Christina Matzke; Benedikt Wirth (University of Bonn, Bonn Graduate School of Economics (BGSE), 2008)
In our model, individual consumers follow simple behavioral decision rules based on imitation and habit as suggested in consumer research, social learning, and related fields. Demand can be viewed as the outcome of a population game whose revision protocol is determined by the consumers' behavioral rules. The consumer dynamics are then analyzed in order to explore the demand side and first implications for a strategic supply side.
Keywords: C61; C62; C79; 330; bounded rationality; social learning; population game; mean dynamic; Absatz; Mikroökonomische Fundierung; Konsumtheorie; Entscheidung bei Unsicherheit; Lernprozess; Evolutionäre Spieltheorie; Theorie